A fair slice of the pie? Problematising the dispersal of government funds to Australian universities. Issue 6 (2nd November 2017) - Heffernan, Troy A.
ABSTRACT: A common theme in higher education research is the factors that affect university funding. Studies frequently examine how universities cope with funding cuts and the changes that have stemmed from operating in a neoliberal age, a period that now sees institutions commonly functioning on a cost/benefit basis. This paper offers an original contribution by using the Australian Federal Government Department of Education and Training's document, Finance 2015: Financial Reports of Higher Education Providers, to problematise the financial assistance individual Australian public universities received from the federal government. The paper acknowledges the factors that can account for some institutions receiving more funding than others but nonetheless highlights the substantial discrepancies concerning government financial contributions that exist between Australia's highest and lowest funded universities. At a time when a performative culture has increasingly become part of higher education, and an institution's research performance is calculable and rankable, it is crucial to Australia's long-term research success that all its universities remain competitive in the race for research and government funding.